1912
DOI: 10.5962/bhl.title.25108
|View full text |Cite
|
Sign up to set email alerts
|

The physiology of protein metabolism

Abstract: after absorption, could be used for rebuilding purposes, and which therefore might be regarded as a stage towards protein regeneration. They held that their view was strengthened by the fact that the increase of the excretion of nitrogen after the administration of leucine did not correspond with the amount of leucine fed, and further that an analogy existed in plant physiology where it was demonstrated that the decomposition products of protein, namely asparagine, leucine and tyrosine could be regenerated int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1915
1915
1969
1969

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 68 publications
1
7
0
Order By: Relevance
“…8, in which the number of meals of a fixed diet were varied from 8 to 2 without seriously affecting the level of N output (Table X). This is consistent with the results of other workers, as reviewed by Cathcart [1921]. It may be further noted that this change in the number of meals in Exp.…”
Section: Discussionsupporting
confidence: 93%
“…8, in which the number of meals of a fixed diet were varied from 8 to 2 without seriously affecting the level of N output (Table X). This is consistent with the results of other workers, as reviewed by Cathcart [1921]. It may be further noted that this change in the number of meals in Exp.…”
Section: Discussionsupporting
confidence: 93%
“…Falta and others (7,4,14) have found that in normal individuals considerable lag in the excretion of nitrogen may follow the superposition of certain proteins on a standard diet. Lag has been attributed to the manufacture of deposit protein and its subsequent utilization in metabolism when the supplementary protein feeding was stopped.…”
Section: Discussionmentioning
confidence: 99%
“…Edema fluid, when present, was considered to contain 90 per cent water (17). 4 The consideration of all of the nitrogen of the stools as catabolic is probably not correct in all instances. For calculating the biological values of proteins the method of Mitchell (15) which involves the deduction of unabsorbed nitrogen from the intake is more accurate.…”
Section: Methodsmentioning
confidence: 99%
“…probably heals as well as one whose labile protein pool overflows with an intake of more than 100 g/day. However, we must agree with Clark (1967) that there is no evidence as yet to show whether moderate protein depletion affects the convalescence of a patient.…”
mentioning
confidence: 82%